Answer:
The solution to the system of equations is (-3, 1)
Step-by-step explanation:
The given system of equations is:
4x + 2y = -10............(1)
3x + 9y = 0..............(2)
Divide equation (1) through by 2
2x + y = -5
Make y the subject of the formula
y = -5 - 2x.........(3)
Substitute equation (3) into equation (2)
3x + 9(-5 - 2x) = 0
3x - 45 - 18x = 0
18x - 3x = -45
15x = -45
x = -45/15
x = -3
Substitute x = 3 into equation (3)
y = -5 - 2(-3)
y = -5 + 6
y = 1
Therefore, the solution to the system of equations is (-3, 1)